The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.2458/56.17771
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Examination of 14CO2 Chamber Methodologies for Sampling at the Soil Surface

Abstract: Radiocarbon is an exceptionally useful tool for studying soil-respired CO 2 , providing information about soil carbon turnover rates, depths of production, and the biological sources of production through partitioning. Unfortunately, little work has been done to thoroughly investigate the possibility of inherent biases present in current measurement techniques, like those present in δ 13 CO 2 methodologies, caused by disturbances to the soil's natural diffusive regime. This study investigates the degree of bia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…This suggests that different collection methodologies did not result in different 14 C ages. Furthermore, it supports our hypothesis that any isotopic fractionation effects caused by the different chamber sampling approaches are either too small to be significant (as reported by Egan et al, ), or are corrected for by using the existing 13 C normalization approach (Stuiver & Polach, ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This suggests that different collection methodologies did not result in different 14 C ages. Furthermore, it supports our hypothesis that any isotopic fractionation effects caused by the different chamber sampling approaches are either too small to be significant (as reported by Egan et al, ), or are corrected for by using the existing 13 C normalization approach (Stuiver & Polach, ).…”
Section: Discussionsupporting
confidence: 89%
“…Because the conditions in the floating chamber differ from the ambient atmosphere, it has been argued that the isotopic composition of the CO 2 lost from the water surface will be altered (see Billett & Garnett, 2010). For example, the mass differences of individual carbon isotopes are known to affect rates of diffusion of CO 2 in air, with 12 CO 2 diffusing at a rate of 1.044 and 1.088 times faster than 13 CO 2 and 14 CO 2 , respectively (Cerling, Solomon, Quade, & Bowman, 1991;Craig, 1953;Egan, Nickerson, Phillips, & Risk, 2014). Although such "mass-dependent" isotopic fractionation effects do alter the 14 C concentration relative to the other isotopes, conventional 14 C age results are corrected for this by normalizing to a standardized δ 13 C of −25‰ (Stuiver & Polach, 1977).…”
mentioning
confidence: 99%
“…Method 1 is actually acceptable for use in the case of surface flux chambers, because unlike soil CO 2 which will always differ from soil production soil-respired CO 2 , conservation of mass dictates that isotopic values of flux must represent soil production so long as the soil is in steady-state (Cerling et al, 1991). While radiocarbon surface flux data need no correction for transport 15 fractionation, researchers should be cautious when using surface flux chambers because they can cause isotopic disequilibrium (Albanito et al, 2012;Egan et al, 2014;Midwood and Millard, 2011;Nickerson and Risk, 2009a). As shown in the Egan et al (2014) study, static chamber methods (i.e.…”
Section: Transferability Across Sampling Methodologiesmentioning
confidence: 99%
“…Gaudinski et al, 2000;Schuur and Trumbore, 2006) This study suggested that the conventional Stuiver and Polach (1977) radiocarbon correction accommodated isotopic fractionation by the sieve. However, under non-steady state conditions, the conventional correction may not actually apply because the 14 CO 2 / 12 CO 2 fractionation factor will not always be a constant multiple of the 13 CO 2 / 12 CO 2 fractionation factor as 25 the system moves from one state to another (Egan et al, 2014).…”
Section: Transferability Across Sampling Methodologiesmentioning
confidence: 99%
See 1 more Smart Citation